Drivers of value addition and product upgrading to shea nuts by collectors in northern Uganda - Akatwetaba, Deborah; Mugonola, Basil; Kasharu, Appolo; Okello, Daniel M.; Egeru, Anthony (African Journal of Science, Technology, Innovation and Development, 2022)
This study assessed the factors associated with value addition and product upgrading of shea nut in northern Uganda. We adopted a cross-sectional research design using a multi-stage sampling approach and a structured interviewer-administered questionnaire to collect data from 252 respondents. The results show that 84% of shea nut collectors practise some level of value addition with 11.5% adding value to all of the shea nuts collected. Over 50% of the shea nut collectors had at least one value-added product with about 3% having four value-added products, the most common products being roasted kernel and crude butter (37.3%). Regression analysis revealed that level of value addition was significantly influenced by gender, age, land under shea cultivation, income, information access, association membership and spot marketing, while the number of value-added products was significantly influenced by age, household size, extension access, information access, association membership, informal marketing, formal marketing and location of shea collector. The findings imply that increasing shea value addition in terms of both proportions allocated to value addition and the number of value-added products require adopting a group approach to provision of value addition and shea processing information. Therefore, we recommend the need to encourage shea actors to form associations focused on value addition.
Keywords: Shea nut; Collectors; Product; Upgrading; Uganda